Fully automated radiosynthesis of [18F]LBT999 on TRACERlab FXFN and AllinOne modules, a PET radiopharmaceutical for imaging the dopamine transporter in human brain - Christine Vala; Céline Mothes; Gabrielle Chicheri; Pauline Magadur; Gilles Viot; Jean-Bernard Deloye; Serge Maia; Yann Bouvet; Anne-Claire Dupont; Nicolas Arlicot; Denis Guilloteau; Patrick Emond; et al. (SpringerOpen, 2020)
Abstract Background Fluorine labelled 8-((E)-4-fluoro-but-2-enyl)-3β-p-tolyl-8-aza-bicyclo[3.2.1]octane-2β-carboxylic acid methyl ester ([18F]LBT999) is a selective radioligand for the in vivo neuroimaging and quantification of the dopamine transporter by Positron Emission Tomography (PET). [18F]LBT999 was produced on a TRACERlab FXFN for the Phase I study but for Phase III and a potent industrial production transfer, production was also implemented on an AllinOne (AIO) system requiring a single use cassette. Both production methods are reported herein. Results Automation of [18F]LBT999 radiosynthesis on FXFN was carried out in 35% yield (decay-corrected) in 65 min (n = 16), with a radiochemical purity higher than 99% and a molar activity of 158 GBq/μmol at the end of synthesis. The transfer to the AIO platform followed by optimizations allowed the production of [18F]LBT999 in 32.7% yield (decay-corrected) within 48 min (n = 5), with a radiochemical purity better than 98% and a molar activity above 154 GBq/μmol on average at the end of synthesis. Quality controls of both methods met the specification for clinical application. Conclusion Both modules allow efficient and reproducible radiosynthesis of [18F]LBT999 with good radiochemical yields and a reasonable synthesis time. The developments made on AIO, such as its ability to meet pharmaceutical criteria and to more easily comply with GMP requirements, make it an optimal approach for the potent industrial production of [18F]LBT999 and future wider use.